Reconstructing Four Centuries of Temperature-Induced Coral Bleaching on the Great Barrier Reef - Kamenos, Nicholas A.; Hennige, Sebastian J. (Frontiers in Marine Science, 2018)
Mass coral bleaching events during the last 20 years have caused major concern over the future of coral reefs worldwide. Despite damage to key ecosystem engineers, little is known about bleaching frequency prior to 1979 when regular modern systematic scientific observations began on the Great Barrier Reef (GBR). To understand the longer-term relevance of current bleaching trajectories, the likelihood of future coral acclimatization and adaptation, and thus persistence of corals, records and drivers of natural pre-industrial bleaching frequency and prevalence are needed. Here, we use linear extensions from 44 overlapping GBR coral cores to extend the observational bleaching record by reconstructing temperature-induced bleaching patterns over 381 years spanning 1620-2001. Porites spp. corals exhibited variable bleaching patterns with bleaching frequency (number of bleaching years per decade) increasing (1620-1753), decreasing (1754-1820) and increasing (1821-2001) again. Bleaching prevalence (the proportion of cores exhibiting bleaching) fell (1670-1774) before increasing by 10% since the late 1790s concurrent with positive temperature anomalies, placing recently observed increases in GBR coral bleaching into a wider context. Spatial inconsistency along with historically diverging patterns of bleaching frequency and prevalence provide queries over the capacity for holobiont (the coral host, the symbiotic microalgae and associated microorganisms) acclimatisation and adaptation via bleaching, but reconstructed increases in bleaching frequency and prevalence, may suggest coral populations are reaching an upper bleaching threshold, a ‘tipping point’ beyond which coral survival is uncertain.